DEVELOPING ENGLISH SYLLABUS FOR TOURISM MANAGEMENT STUDENTS - Soraya Grabiella Dinamika; Elitaria Bestri Agustina Siregar (Universitas Negeri Padang, 2016)
This research aimed at developing a one-semester ESP syllabus, particularly for the tourism management students of the second semester in academic year of 2015/2016 of STIM Sukma Medan. Therefore, the research and development (R&D) design was conducted to investigate the students’ needs in ESP class on the second semester and to develop the appropriate syllabus. There were two instruments used to collect the data, namely; questionnaire and interview. The questionnaire was given to 12 prospective students who would attend ESP class on second semester. Meanwhile, the interviews were projected to three different participants, namely an ESP lecturer, two prospective students, and a student working in the tourism field. Based on the data revealed, it was found that the students need to extend their speaking and writing skills. Speaking was used to communicate with the clients in spoken register in the future work field. Meanwhile, writing was used to communicate with the clients in written register in the future work field. Therefore, the development of syllabus was focus on speaking and writing followed by listening and reading respectively.